2016
DOI: 10.3389/fpsyg.2016.01222
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Tendency to Use Emotion Regulation Strategies and Their Relation to Depressive Symptoms in Chinese Adolescents

Abstract: The process model of emotion regulation posits that the tendency to use cognitive reappraisal is associated with positive outcomes (e.g., greater positive emotion) while the tendency to use expressive suppression is associated with adverse outcomes (e.g., greater negative emotion). Many studies using adult samples support this theory. However, the development of the tendency to use cognitive reappraisal/expressive suppression and how these tendencies relate to depressive symptoms in adolescents remain unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 29 publications
4
31
0
1
Order By: Relevance
“…Third, a negative relation was shown between cognitive reappraisal and depressive symptoms. This finding is in line with prior research (Sai et al, ), which suggested that increased use of cognitive reappraisal correlates to decreased depressive symptoms. Fourth, the result that expressive suppression positively related with depressive symptoms is in accordance with previous findings about adolescents (Brenning et al, ; Sai et al, ), which indicated that the more expressive suppression adolescents use, the more depressive symptoms they experience.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Third, a negative relation was shown between cognitive reappraisal and depressive symptoms. This finding is in line with prior research (Sai et al, ), which suggested that increased use of cognitive reappraisal correlates to decreased depressive symptoms. Fourth, the result that expressive suppression positively related with depressive symptoms is in accordance with previous findings about adolescents (Brenning et al, ; Sai et al, ), which indicated that the more expressive suppression adolescents use, the more depressive symptoms they experience.…”
Section: Discussionsupporting
confidence: 93%
“…Participants rated the items on a 7‐point Likert scale (from “1 = strongly disagree” to “7 = strongly agree” ). A Chinese version of this questionnaire which has been validated by adults and teenagers was used (e.g., Sai et al, ). In this study, Cronbach's alpha coefficients were 0.71 for the cognitive reappraisal subscale and 0.66 for the expressive suppression subscale.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations